2016
DOI: 10.1039/c6ra15385b
|View full text |Cite
|
Sign up to set email alerts
|

A stretchable sensor platform based on simple and scalable lift-off micropatterning of metal nanowire network

Abstract: We describe a simple, precise and scalable micropatterning approach of conductive nanomaterials (CNs) based on a synergetic combination of lift-off process and wet coating of CNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Direct fabrication of thin metallic films with high resolution features on PDMS is challenging 23 . The large coefficient of thermal expansion (CTE) (~0.31% per K) of PDMS compared to conventional photoresists causes significant expansion mismatch that results in the crack formation during lithography 24 – 27 . The alternate solution of using wet etching of the metal deposited on PDMS leads to undercutting due to the isotropic etching reaction, which restricts both the resolution and density of the electrodes 28 – 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Direct fabrication of thin metallic films with high resolution features on PDMS is challenging 23 . The large coefficient of thermal expansion (CTE) (~0.31% per K) of PDMS compared to conventional photoresists causes significant expansion mismatch that results in the crack formation during lithography 24 – 27 . The alternate solution of using wet etching of the metal deposited on PDMS leads to undercutting due to the isotropic etching reaction, which restricts both the resolution and density of the electrodes 28 – 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Microcracks resulted from the differences in CTE remain unresolved to date based on known literatures. However, a recent work showed that these microcracks (typical width < 1 μm) do not present major concerns when patterning silver nanowires which are too large to penetrate through 50 Examples of gold patterning fabricated via wet etching have been shown by several authors. Meacham et al had constructed an elastic multi-electrode array based on PDMS with the method described above 51 .…”
Section: Repurposing Conventional Manufacturing Techniques For Stretcmentioning
confidence: 99%
“…Jeong et al . reported reliable micropatterning method of AgNWs by the combination of lift-off process and spray coating process 33 . In addition, Ahn et al .…”
Section: Introductionmentioning
confidence: 99%